ETHICAL VALUES IN THE LOGIC OF ASSESSMENTS AND NORMS (Scientific journal of the Fergana State University, 2023)
This article considers ethical values from the perspective of the logic of assessments and norms, as well as an analysis of subjective approaches to ethical processes of assessments and norms. In addition, the research work of assessments and norms based on logical laws and principles is reviewed.